Recurrent Pleural Effusions Occurring in Association with Primary Pulmonary Amyloidosis - Lauren Tada; Humayun Anjum; W. Kenneth Linville; Salim Surani (Case Reports in Pulmonology)
Recurrent pleural effusions occurring in association with immunoglobulin light chain amyloidosis and not associated with amyloid cardiomyopathy are rare. These portend an overall poor prognosis with mean survival time of approximately 1.8 months. We hereby report a case of a 59-year-old Caucasian female with recurrent pleural effusions and an ultimate diagnosis of pulmonary amyloidosis in association with plasma cell myeloma. The optimal treatment for recurrent pleural effusions in amyloidosis has not been determined; however, our patient responded to therapy with Cyclophosphamide-Bortezomib- (Velcade-) Dexamethasone (CyBorD) and had no repeat hospitalizations or recurrence of pleural effusion at four-month follow-up after initiation of therapy.